An analysis of synonymous compounds appeared in Khaosaw, Phra Aphaimani and Srisuwan - ปัญจบุรี, ณัฐพงษ์ (Community and Social Development Journal, 2019)
The study of compound words analysis appeared in Phra Aphai Mani and Srisuwan aims to investigate the compound words with the occurrences of two words, three words, four words, and euphonic couplet. It is also intended to study the compound words created from official Thai accent, Northen Thai accent, Pali-Sansakrit, including the compound words which contain similar and opposite meanings that appeared in Phra Aphai Mani and Srisuwan Khaosaw. In this case, the primary source to provide information for this study is Phra Aphai Mani and Srisuwan Khaosaw book written by PrayaPhromwo-harn in Lanna characteristic version with 143 pages that firstly published at American press in 1930. The results of the study reveal that there were several types of compound words as following. For two words type, there were 449 glossaries. For three words type, there were 152 glossaries. For four words type, there were 143 glossaries. For over four words type, there were 6 glossaries. In addition, for the creation of different languages compound words, namely official Thai accent, Northen Thai accent, Pali-Sansakrit, there were two words type with 105 glossaries. For three words type, there were 35 glossaries. For four words type, there were 6 glossaries. For the compound words divided by types of meanings, there were the same meaning compound words with 253 glossaries. The compound words with similar meanings with 343 glossaries, and opposite meanings with 15 glossaries.